Les chargés de TD/TP ont-ils tous les mêmes inquiétudes avant leurs premières interventions face aux étudiants ? - Joelle Demougeot-Lebel; Cathy Perret (Recherches en Éducation)
This paper focuses on worries of beginners’ academics in relation with their conceptions on teaching and leaning. It’s based on empirical studies contracted in university of Burgundy. Some of these worries are common to all, and some are dependent from conceptions. Worries related to organised student participation are found more frequently in instructors who have a student centred representation of teaching and learning